Minat, Motivasi dan Kesadaran Hidup Sehat Masyarakat Dalam Olahraga Rekreasi Car free Day di Kota Semarang (Universitas Negeri Semarang, 2021)
The purpose of this research is to determine the community’s interest, motivation and awareness of healthy life in the city of Semarang on participating in recreational sports through car free days. Population and sample in this research is a community in the city of Semarang, who take part in Car Free Day activity at Pahlawan street, Pandanaran street, Simpang Lima field area, Indonesia Kaya green open space in the city of Semarang. The technique of data collection conducted in this research is the observation by using questionnaires and data analysis methods used in this study is the analysis of deskriptif presentage. The result showed that the public’s interest in participating in Car Free Day recreational sports in the city of Semarang with score presentage is 73,54%. This can be seen in the data tabulation that an average score of factor of intrinsic is 82,35%, with 72.25% chose the factor of amenities and 59,25% is the environment factor and the last one friend factor has 69,25% as the factors. For the motivation of the community in participating in Car Free Day recreational sports in the city of Semarang with score persentage is 79,34% with the major factors that dive was a factor as much as attention 81,87%, the relevance factor as many as 84,87%, self confidence as much as 73,75%, and the satisfaction factor as much 76,87%. For the health of the community in participating in Car Free Day recreational sports in the city of Semarang with score persentage is 78,86% the data tabulation that an average score of factor of health status is 72,12%, as many as 77,25% chose the factors of healthy environment, as much of the 77,67% vote of healthy behavior and as much as 84,35% chose knowledge factors. Summary of the results of this research is the Semarang city community had a high persentage of interest 73,54%, the percentage of motivation is 79,34% and have a high healthy life awareness with the percentage 78,86%.